THERMAL ANALYSIS OF CARBOXYL-MODIFIED COBALT AND CALCIUM METAL PHTHALOCYANINE PIGMENTS - Nuritdinov, Abdullazizbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this study, the thermal behavior of the carboxyl-functionalized phthalocyanine pigment containing cobalt/calcium metal centers was investigated using TG/DTA techniques in the temperature range of 25–700 °C. The thermogravimetric (TG) curve revealed a two-stage decomposition pattern. The first mass-loss event, occurring between 18.47 and 326.94 °C, accounted for 1.828 mg (52.909%) and corresponds to the removal of physically adsorbed moisture, residual solvents, and the initial decarboxylation of the modified phthalocyanine framework. The second stage, observed within 326.94–701.09 °C, resulted in an additional mass loss of 0.929 mg (26.889%) and is attributed to the progressive breakdown of the macrocyclic aromatic structure. The DTA thermogram exhibited a pronounced endothermic peak at 217.25 °C, associated with carboxyl group detachment and structural rearrangements, followed by a strong exothermic peak at 613.58 °C, indicating deep oxidative degradation of the phthalocyanine macrocycle. These results collectively confirm that the pigment undergoes primary decomposition related to its carboxyl functionalities, followed by extensive aromatic degradation at higher temperatures. Overall, the obtained TG/DTA profiles demonstrate that the modified metal phthalocyanine pigment possesses high thermal stability, maintaining significant structural integrity even above 600 °C, which is a favorable characteristic for applications requiring enhanced heat resistance.